Rethinking education choices: The effect of surveys - FACCHINELLO, Luca (Institutional Knowledge at Singapore Management University, 2019)
Can surveys affect human capital investments? This paper examines whether individual education choices and outcomes are affected by a survey posing questions related to expectations and forward-looking behavior. We have administrative data for the whole Swedish population to which an extensive education survey was administered to randomly drawn samples of 3rd graders. This constitutes a randomized social experiment for testing whether responding to survey questions alters behavior. We observe complete educational and labor market histories until the individuals are 31-41 years old. We have exogenous variation in the timing of first surveys and when an additional survey was administered to parents. The causal effect of the survey on both short- and long-term outcomes is generally not significantly different from zero. We find, however, that being surveyed increases educational attainment and job stability in the early career for those with low parental education. We also assess heterogeneity in estimated causal effects in order to get at potential mechanisms. The patterns indicate the importance of increased awareness.